Regulations Harmonization of Proposal and Stipulation of Special Economic Zone in Indonesia - Muh Ali Masnun; Radhyca Nanda Pratama (LAW REFORM, 2020)
The acceleration of economic development in Indonesia cannot be separated when the government implements a Special Economic Zone (KEK) policy by using legal instruments in it. The purpose of this study is to examine the harmonization of regulations related to the proposal and determination of SEZ in Indonesia. This study uses normative legal research, using primary and secondary legal materials. First analysis, the provisions of business entities as proposers for SEZ need to be reviewed because they have a cumulative meaning. Second, private business entities proposing SEZ need to be limited, especially in important areas relating to the life of the wider community. Third, the determination of SEZ by the government (Article) needs to pay attention to RTRW, protected forest areas, and / or analysis of environmental impacts. Fourth, stipulation without a proposal stage is contrary to the principle of kinship. Fifth, Article 8 of the UU KEK is inconsistent with the PP on the Implementation of SEZ and the 2011 Minister of Coordinating Ministry for Guidelines for SEZ Proposals. Sixth, the SEZ proposal by the Minister of Research, Technology and Higher Education needs to be scrutinized and analyzed in depth in the process of its determination.